Real‐time brain stroke detection through a learning‐by‐examples technique—An experimental assessment. Issue 11 (November 2017) - Salucci, Marco; Vrba, Jan; Merunka, Ilja; Massa, Andrea
Abstract: The real‐time detection of brain strokes is addressed within the Learning‐by‐Examples (LBE) framework. Starting from scattering measurements at microwave regime, a support vector machine ( SVM ) is exploited to build a robust decision function able to infer in real‐time whether a stroke is present or not in the patient head. The proposed approach is validated in a laboratory‐controlled environment by considering experimental measurements for both training and testing SVM phases. The obtained results prove that a very high detection accuracy can be yielded even though using a limited amount of training data.